1985
DOI: 10.1177/00220345850640080401
|View full text |Cite
|
Sign up to set email alerts
|

Dental Pulp Response to Bacterial Cell Wall Material

Abstract: Lipopolysaccharides (LPS) from Bacteroides oralis and Veillonella parvula and cell wall material from Lactobacillus casei were studied for their capacity to induce leukocyte migration in the dental pulp and in an implanted wound chamber. Three adult monkeys were challenged using lyophilized material sealed into buccal Class V cavities prepared in dentin. Pulp tissue responses were observed histologically eight and 72 hours after initiation of the experiment. Subjacent to cut dentinal tubules, bacterial materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

1987
1987
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 16 publications
(17 reference statements)
0
30
0
1
Order By: Relevance
“…Based on experimental pulpitis studies, C3a and C5a generated from complement activation were thought to be important virulence factors of cariogenic bacteria that elicit neutrophil accumulation in the Arthus reaction (2,3,5,30). Recent studies, however, showed that the presence of an intact complement cascade is neither necessary nor sufficient to trigger or propagate the Arthus reaction (136,137).…”
Section: Other Virulence Factors Of Caries Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on experimental pulpitis studies, C3a and C5a generated from complement activation were thought to be important virulence factors of cariogenic bacteria that elicit neutrophil accumulation in the Arthus reaction (2,3,5,30). Recent studies, however, showed that the presence of an intact complement cascade is neither necessary nor sufficient to trigger or propagate the Arthus reaction (136,137).…”
Section: Other Virulence Factors Of Caries Pathogensmentioning
confidence: 99%
“…Although bacteria or their cell-wall components such as LPS are capable of passing through tubules to induce inflammatory responses in the dental pulp (2,4,5,30), the thickness of dentin can greatly reduce the concentration of bacterial proteins and the amount of LPS that reaches the pulp (31,148,149). We infiltrated commercial LTA preparations from S. mutans through dentinal blocks using fluid filtration and observed that the dentin permeability decreased with time (Fig.…”
Section: Remaining Dentin Thickness and Tubular Permeabilitymentioning
confidence: 99%
“…The mechanisms involved in the initiation and monitoring of the pulp inflammatory defense are, however, not well understood. Experimental data have shown that antigens from oral micro-organisms induce inflammatory reactions in the pulp tissue across exposed dentin (Bergenholtz and Lindhe, 1975;Bergenholtz, 1977;Warfvinge et al, 1985), but the basis for the initial recognition of antigens and how they are processed in the pulp has not been clearly demonstrated.…”
mentioning
confidence: 99%
“…When deep caries are present, some odontoblasts may survive and participate in pulpal responses by forming new dentin (24,25). However, there are few reports on the effect of LPS on dentin matrix protein expression.…”
Section: Discussionmentioning
confidence: 99%